Arcadia (1993) de Tom Stoppard : la passion du bilan - Nicole Boireau (Sillages Critiques)
Based on a fake love affair, on a literary enigma and on the illusory solution of Fermat’s theorem, Tom Stoppard’s Arcadia takes place in an imaginary estate which, like a palimpsest bears the marks of stylistic changes. Structurally and thematically, the play theatricalises all scientific and critical debates since Newton. Arcadia operates like a blank page, an empty form paradoxically rooted in the real world. Stoppard combines the comedy of manners form with the whodunit to build a trompe-l’œil play, based on a dual time structure, involving both literary figures from the past and present-day intellectuals, who try to work out the enigmas at the heart of the play. Arcadia’s textual nature is based on the mise en scène of language. Scientific discourse generates order and disorder, both being open to chance. Young Thomasina’s accidental death is creative of emotion. The play problematises the contingency of all events, the passing of time as well as a deeply-rooted sense of permanence.